Household labour allocation to forest extraction and other activities in areas adjacent to tropical forests: The case of Kakamega forest, Western Kenya - Sikei, G.; Mburu, J.; Kibiwot Lagat, J. (Inderscience Publishers, 2008)
Communities adjacent to forests are faced with a challenge of balancing their labour allocation decisions to the different household activities. This study involves an empirical examination of the determinants of households labour allocation decisions with respect to three different activities identified as important in the study area; agriculture, forest and non-farm. This was done by estimating a labour share model similar to standard models of commodity or factor demand, such as the Almost Ideal Demand Systems (AIDS) model. Data on household characteristics and key policy parameters directly or indirectly affecting labour allocation decisions were collected between March and May 2007. A semi-structured questionnaire was used to collect data from a random sample of 140 households. From the findings, it was evident that household members respond positively to wage returns. The positive relationship between the returns to forest use and forest labour share provides a cautionary message for policy-makers and other stakeholders concerned with the fate of the Kakamega forest. In the short term, it seems probable that the returns to forest use will increase as the aggregate demand for forest products rises and supply declines. The study findings suggest that, with improved economic well-being, households become less reliant on forests for their livelihoods. Since reduced forest reliance is positively related with a reduced demand for forest products, these findings suggest a complementary relationship between strategies aimed at poverty alleviation and those aimed towards forest conservation.